2014
DOI: 10.1371/journal.pone.0099845
|View full text |Cite|
|
Sign up to set email alerts
|

Data Sharing Reveals Complexity in the Westward Spread of Domestic Animals across Neolithic Turkey

Abstract: This study presents the results of a major data integration project bringing together primary archaeozoological data for over 200,000 faunal specimens excavated from seventeen sites in Turkey spanning the Epipaleolithic through Chalcolithic periods, c. 18,000-4,000 cal BC, in order to document the initial westward spread of domestic livestock across Neolithic central and western Turkey. From these shared datasets we demonstrate that the westward expansion of Neolithic subsistence technologies combined multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 47 publications
2
103
0
3
Order By: Relevance
“…Likewise, it is understood that domestic pigs are encountered at the first Neolithic settlements in the Lakes District and Central-west Anatolia and that local pigs were also domesticated. It has also been suggested that the existence of domesticated pig dates to the early 6 th millennium BC in Northwest Anatolia, and the method and impetus for the domestication of pig then passed through Central-west Anatolia (Ottoni et al 2013;Arbuckle et al 2014). The appearance of domesticated pig is not the only novelty in Northwest Anatolia in the early 6 th millennium BC.…”
Section: Subsistence Strategiesmentioning
confidence: 99%
“…Likewise, it is understood that domestic pigs are encountered at the first Neolithic settlements in the Lakes District and Central-west Anatolia and that local pigs were also domesticated. It has also been suggested that the existence of domesticated pig dates to the early 6 th millennium BC in Northwest Anatolia, and the method and impetus for the domestication of pig then passed through Central-west Anatolia (Ottoni et al 2013;Arbuckle et al 2014). The appearance of domesticated pig is not the only novelty in Northwest Anatolia in the early 6 th millennium BC.…”
Section: Subsistence Strategiesmentioning
confidence: 99%
“…These methods hold tremendous interpretive advantages, yet their complications and limitations should also be acknowledged, a point which all of the authors discuss. Quantitative synthesis of available faunal datasets (Dusseldorp 2016) as well as revisiting Bold^collections from new theoretical and methodological angles (Antonites et al 2016;Ashley et al 2016;Grody 2016) will become common archaeozoological practice and serve as a reminder to present data and curate collections in ways that will enable future study (see e.g., Arbuckle et al 2014;Atici et al 2013;Jones and Gabe 2015). L i n k e d t o s t a n d a r d i s e d a n d a c c e s s i b l e archaeozoological data is the issue of methodological transparency, and the critical evaluation of data quality (Gobalet 2001;O'Connor 1996;Wolverton 2013).…”
Section: Current Approaches To the Archaeozoology Of The Last 2000 Ymentioning
confidence: 99%
“…Today, the field is shifting towards better integrating research designs and results with other archaeological datasets (e.g., Hamilton and Thomas 2012;Maltby 2006;VanDerwarker and Peres 2010). Computer technology now enables incorporation, comparison and quantitative analysis of large faunal datasets on a scale not possible before (e.g., Arbuckle et al 2014;Orton et al 2014). Methodological advances-such as the development of Zooarchaeology by Mass Spectrometry or ZooMS (Buckley et al 2009) and use-wear analysis (Évora 2015)-are helping archaeozoologists to break through the confines of macroscopic examination.…”
Section: Introductionmentioning
confidence: 99%
“…This initiative has the potential to enable comparisons between a large number of existing databases without learning project-specific code. Kansa specifically discusses an example where this was successful across a large group of independent zooarchaeologists conducting research in Turkey (Arbuckle et al 2014). The study is part of the larger Open Context project 6 , which is demonstrating the benefits of designing digital systems that can reconcile a diverse range of highly specific disciplinary terminologies.…”
Section: Editorialmentioning
confidence: 99%